Effects of Fructus mume Extract on MAPK and NF-κB Signaling and the Resultant Improvement in the Cognitive Deficits Induced by Chronic Cerebral Hypoperfusion. (30th December 2012) - Jeon, Won Kyung; Ma, Jinhua; Choi, Bo-Ryoung; Han, Seol-Heui; Jin, Qinghao; Hwang, Bang Yeon; Han, Jung-Soo
Abstract : Fructus mume ( F. mume ) has been used as a medicinal food in Japan and has been reported to have anti-inflammatory effects in inflammatory bowel disease and macrophage-mediated inflammation. We investigated the effects of F. mume extracts on cognitive dysfunction in rats with chronic cerebral hypoperfusion and the molecular mechanisms underlying these effects. Chronic cerebral hypoperfusion was induced in male Wister rats by bilateral common artery occlusion (BCCAo). Daily administration of F. mume extracts was started on day 20 after post-BCCAo and continued for 40 days. The status of hippocampus-dependent memory was evaluated in control rats, rats with chronic cerebral hypoperfusion, and rats with chronic cerebral hypoperfusion that were administered F. mume . The levels of microglial activation were measured in the hippocampus and the fimbria of hippocampus, and expression levels of hippocampal mitogen-activated protein kinase (MAPK) and nuclear factor- κ B (NF- κ B) were examined. Rats that received chronic cerebral hypoperfusion showed spatial memory impairments relative to the control rats; these impairments were reduced by daily administration of F. mume . Administration of F. mume mitigated the microglial activation and alterations of hippocampal MAPK and NF- κ B signaling in the rats with chronic cerebral hypoperfusion. These results indicate that F. mume may possess therapeutic potential for the prevention of vascular dementia via inhibition of inflammatory processes.